The attack and defense of weakest-link networks - Dan Kovenock; Brian Roberson; Roman M. Sheremeta (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper experimentally examines behavior in a two-player game of attack and defense of a weakest-link network of targets, in which the attacker's objective is to successfully attack at least one target and the defender's objective is diametrically opposed. We apply two benchmark contest success functions (CSFs): the auction CSF and the lottery CSF. Consistent with the theoretical prediction, under the auction CSF, attackers utilize a stochastic 'guerilla warfare' strategy - in which a single random target is attacked - more than 80% of the time. Under the lottery CSF, attackers utilize the stochastic guerilla warfare strategy almost 45% of the time, contrary to the theoretical prediction of an equal allocation of forces across the targets.
Keywords: C72; C91; D72; D74; 330; Colonel Blotto; conflict resolution; weakest-link; best-shot; multi-dimensional resource allocation; experiments; Konflikt; Spieltheorie; Netzwerk; Test; Theorie